A laser-cutting-based manufacturing process for the generation of three-dimensional scaffolds for tissue engineering using Polycaprolactone/Hydroxyapatite composite polymer. (June 2019) - Schmid, Jakob; Schwarz, Sascha; Fischer, Martina; Sudhop, Stefanie; Clausen-Schaumann, Hauke; Schieker, Matthias; Huber, Robert
A manufacturing process for sheet-based stacked scaffolds (SSCs) based on laser-cutting (LC) was developed. The sheets consist of Polycaprolactone/Hydroxyapatite (PCL/HA) composite material. Single sheets were cut from a PCL/HA foil and stacked to scaffolds with interconnecting pores of defined sizes. HA quantities up to 50% were processable with high reproducibility, while the accuracy was dependent on the applied laser power. The smallest achievable pore sizes were about 40 µm, while the smallest stable solid structures were about 125 µm. The human mesenchymal stem cell line SCP-1 was cultured on the manufactured PCL/HA scaffolds. The cells developed a natural morphology and were able to differentiate to functional osteoblasts. The generation of PCL/HA SSCs via LC offers new possibilities for tissue engineering (TE) approaches. It is reliable and fast, with high resolution. The SSC approach allows for facile cell seeding and analysis of cell fate within the three-dimensional cell culture, thus allowing for the generation of functional tissue constructs.